La impronta del exilio intelectual republicano español en América Latina: Las cátedras aztecas, el asociacionismo porteño y la nostalgia peninsular en la Mayor de las Antillas - Savín, Claudia Sánchez (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
The present work focalises on the generality of the Spanish republican intellectual exile in Latin America since 1939 and its aim is to expose shortly the tasks and contributions more meaningful and distinctive of those exiles in Mexico, Argentina and Cuba, starting from the concrete historical conditions of each of these destinations.